The Defeat of the Iraq’s Total War Strategy Under the Regime of Saddam Hussein in the 2003 U.S.-Led Invasion: A Reflection - Dianata Panji Prasugi; Agung Risdhianto; Fauzia G. Cempaka (International Journal of Social Science and Community Service, 2026)
The United States (US) along with its western coalition partners carried out the Iraqi invasion in 2003 to topple down President Saddam Hussein who was considered a threat to the international community based on accusations of possession of weapons of mass destruction and his association with the 9/11 terrorist attacks. During the invasion, the Iraqi troops were easily defeated through a military approach by the coalition. The primary objective of this scholarly work is to isolate those variables that rendered Iraqi troops susceptible to swift subjugation. A qualitative methodology, grounded in documentary analysis from printed and online sources such as monographs, scholarly journals, and news archives, was utilised to conduct the inquiry. The resultant analysis identifies several interlocking explanations for Iraq’s decisive defeat in the 2003 American-led offensive. These include a catastrophic failure of foresight on the part of Saddam Hussein, his diversionary focus on latent internal opposition, and the inept formulation and deployment of Iraq’s military doctrines. Concurrently, the overwhelming materiel and strategic ascendancy of the coalition forces proved decisively advantageous. This reflection underscores that the effective implementation of a total war strategy demands detailed planning and due attention to non-military elements of national defense, a consideration with direct relevance for future defense strategy formulation.